A Belgian Imam Training: Mission Impossible? - Franken, Leni (Eurostudia, 2020)
Over the past decades, the number of (practicing) Muslims increased visibly in Belgium, but present Church-State regulations are not adequately adapted to accommodate the diversity of Muslim communities. This has also repercussions for the training of imams. In this contribution, I will briefly sketch the state of the art of this training in Belgium. In order to do so, I will start with an elaboration of Church-State relations in Belgium, where Islam has been one of the seven recognized religions since 1974. Subsequently, attention will be given to the local recognition of mosques and to recent changes on this matter. Furthermore, I will focus on the recent attempt to establish a ‘Belgian’ imam-training and on the reasons for its failure. Finally, some recommendations for improvement will be made.